Characteristics and outcome of patients transported by police to emergency departments under section 351 of the Mental Health Act 2014 (Vic). (12th October 2021) - Ward, Beth; Kollios, Jason; Smith, Fiona; Klim, Sharon; Senz, Ainslie; Kelly, Anne‐Maree
Abstract: Objective: To determine characteristics, precipitating circumstances, clinical care, outcome and disposition of patients brought to the ED under section 351 (s351, police detention and transport) powers of the Mental Health Act 2014 (Vic) (MHAV). Methods: This is an observational cohort study conducted in two metropolitan teaching hospitals in Victoria. Participants were adult patients brought to ED under s351 of the MHAV. Data collected included demographics, event circumstances, pre‐hospital and ED interventions and outcome. Analyses are descriptive. Results: The present study included 438 patient encounters. Median age was 34 years. In 84% of encounters (368/438) patients were co‐transported with ambulance. The most common primary reason for detainment was suicide risk/intent (296/438, 67.6%) followed by abnormal behaviour without threat to self or others (92/438, 21%). In ED, parenteral sedation was administered in 11% (48/438). Physical restraint was applied in 17.6% (77/438). Psychiatric admission was required in 23.5% (103/438). In 63 cases, psychiatric admission was involuntary (14.4%). Most patients (297/438, 67.8%) were discharged home. A subset of patients had recurrent s351 presentations. Eighteen (5.6%) patients accounted for 22% (96/438) of all events. Conclusion: Most patients brought to ED under s351 of the MHAV had expressed intention to self‐harm, did not require medical intervention and were discharged home. It could be questioned whether the current application of s351 is consistent with the least restrictive principles of the MHAV, especially as there is no apparent monitoring or reporting of the use of these powers. There were a concerning number of patients with multiple s351 events over a short period. Abstract : Most patients brought to ED under section 351 (s351) of the Mental Health Act 2014 (Vic) had expressed intention to self‐harm, did not require medical intervention and were discharged home. It could be questioned whether the current application of s351 is consistent with the least restrictive principles of the Mental Health Act 2014 (Vic), especially as there is no apparent monitoring or reporting of the use of these powers. There were a concerning number of patients with multiple s351 events over a short period.